Edukasi Pengelolaan Sampah Sisa Makanan (Organik) untuk Pemuda Kota Batam - Sartikha, Sartikha; Maria, Maria; Rokhayati, Yeni; Santiputri, Metta; Zega, Selly Artaty; Mufida, Miratul Khusna; Uperiati, Alena; Supardianto, Supardianto; Lumombo, Liony (Politeknik Negeri Batam, 2024)
Environmental-friendly organic waste management is crucial for supporting sustainability, especially with the high volume of household waste. This community service project aims to educate the public, particularly the youth, about organic waste management through the use of eco enzyme technology. The education process involves eco enzyme practitioners and youth, facilitated by online-accessible video tutorials and social media campaigns to expand the reach of the information. Various activities, including socialization, education, and a challenge to create eco enzyme tutorial videos, were conducted to enhance participants' understanding and involvement. Evaluation through questionnaires completed by 156 respondents showed a significant increase in participants' knowledge regarding eco enzyme, its preparation methods, and benefits. The level of interest in using eco enzyme reached 94.23%, and the perceived benefits of the socialization process were 95.51%. Thus, this project successfully raised awareness and encouraged youth participation in sustainable organic waste management, which is expected to contribute positively to the environment in Batam City, Riau Island, Indonesia.